Elementos articuladores em artigo de opinião: uma experiência com sequência didática no ensino médio - Ana Maria de Carvalho Leite (2009)
In this work, we analyzed the results of the application of a didactic sequence with opinion article, proposed by the Portuguese Olympiad 2008, with students of the third class of a public high school of the Minas Gerais. We try to answer to the following question: until point the utilization of a new methodology, with activities systematized of reading and writing, having for base the characteristics of a textual gender, it can contribute for the capacities development of the student as texts producer? We specifically observe the change in the articulators elements use in opinion texts produced by submitted students to a didactic sequence about opinion article. The matter was motivated by our experience in the mastership and for official data, according to which ones great part of the students of the public school does not dominate a knowledges set, abilities and competences related to reading and writing procedures, compatible with your education period. The investigation it guided by the studies of the Textual Linguistics about text and textual articulation, as well as by the current theoretician-methodological tendencies contemplated in the National Curricular Parameters and in the Common Portuguese Basic Contents. We follow the experiments model of with two students' belonging groups to two distinct classes. The group A, the one of control, did not take part in the Olympiad and produced a text. The group B took part in the didactic sequence, during which produced initial and final texts. The texts from both groups were submitted the quantitative and qualitative analyses, in which we examined the uses of the articulators elements and the own aspects of the opinion article. To the final cross the data, concerning about of which did a reflection about that indicated, having in mind the lifted matter. Regarding the articulators elements, the analyses indicated in the in the texts of the group controls and in the initial texts of the experimental group the predominant use of markers of cause relationship and consequence and of restriction, strategies considered basic in argumentative statements. After the application of the didactic sequence, we verified in some final texts of the experimental group the occurrence of articulator elements, that they didn't appear in the initial texts, besides the most appropriate use of the articulators elements used in the initial texts. We believed, therefore, that the activities proposed at the workshops of the didactic sequence, although no accomplished in ideal conditions, have contributed to the progress in the use of those resources, that for its time, they carted better cohesive effects in the students' texts. As for the comparison between the traditional practice of written production and the methodology of the didactic sequence, the results appeared for the still need to treat the textual production as a process, which she can do through sequential activities. However, for that work to be effective, countless factors that include the planning, the elaboration and the application of a didactic sequence should be observed. Finally, we hoped these results can serve as base for new reflections that involve, mainly, the relationships between linguistic studies and the teaching of the Portuguese Language.